Requirements for nucleocapsid-mediated regulation of reverse transcription during the late steps of HIV-1 assembly - Racine, Pierre-Jean (Sci Rep, 2016)
HIV-1 is a retrovirus replicating within cells by reverse transcribing its genomic RNA (gRNA) into DNA. Within cells, virus assembly requires the structural Gag proteins with few accessory proteins, notably the viral infectivity factor (Vif) and two copies of gRNA as well as cellular factors to converge to the plasma membrane. In this process, the nucleocapsid (NC) domain of Gag binds to the packaging signal of gRNA which consists of a series of stem-loops (SL1-SL3) ensuring gRNA selection and packaging into virions. Interestingly, mutating NC activates a late-occurring reverse transcription (RT) step in producer cells, leading to the release of DNA-containing HIV-1 particles. In order to decipher the molecular mechanism regulating this late RT, we explored the role of several key partners of NC, such as Vif, gRNA and the cellular cytidine deaminase APOBEC3G that restricts HIV-1 infection by targeting the RT. By studying combinations of deletions of these putative players, we revealed that NC, SL1-SL3 and in lesser extent Vif, but not APOBEC3G, interplay regulates the late RT.